Affordable bathroom upgrades : transform your bathroom on a small budget - Cory, Steve; Slavik, Diane (Upper Saddle River, N.J. : Creative Homeowner, 2012)
Contains inexpensive design ideas and projects to upgrade a bathroom.
"Easy upgrades for: storage, vanities, cabinets, sinks, faucets, tubs and showers, lighting, flooring & more"--Cover.
Includes index.
Keywords: Bathrooms -- Remodeling -- Amateurs' manuals; Bathrooms -- Design and construction; Bathrooms -- Remodeling -- Handbooks, manuals, etc; Bathrooms -- Design and construction